Chronic Cerebral Hypoperfusion Induces Vascular Plasticity and Hemodynamics but Also Neuronal Degeneration and Cognitive Impairment. Issue 8 (August 2015) - Jing, Zhen; Shi, Changzheng; Zhu, Lihui; Xiang, Yonghui; Chen, Peihao; Xiong, Zhilin; Li, Wenxian; Ruan, Yiwen; Huang, Li'an
Chronic cerebral hypoperfusion (CCH) induces cognitive impairment, but the compensative mechanism of cerebral blood flow (CBF) is not fully understood. The present study mainly investigated dynamic changes in CBF, angiogenesis, and cellular pathology in the cortex, the striatum, and the cerebellum, and also studied cognitive impairment of rats induced by bilateral common carotid artery occlusion (BCCAO). Magnetic resonance imaging (MRI) techniques, immunochemistry, and Morris water maze were employed to the study. The CBF of the cortex, striatum, and cerebellum dramatically decreased after right common carotid artery occlusion (RCCAO), and remained lower level at 2 weeks after BCCAO. It returned to the sham level from 3 to 6 weeks companied by the dilation of vertebral arteries after BCCAO. The number of microvessels declined at 2, 3, and 4 weeks but increased at 6 weeks after BCCAO. Neuronal degeneration occurred in the cortex and striatum from 2 to 6 weeks, but the number of glial cells dramatically increased at 4 weeks after BCCAO. Cognitive impairment of ischemic rats was directly related to ischemic duration. Our results suggest that CCH induces a compensative mechanism attempting to maintain optimal CBF to the brain. However, this limited compensation cannot prevent neuronal loss and cognitive impairment after permanent ischemia.